Clinical characteristics and survival in idiopathic pulmonary fibrosis and connective tissue disease-associated usual interstitial pneumonia - Alhamad, Esam H. (Journal of Thoracic Disease; Vol 7, No 3 (March 30, 2015): Journal of Thoracic Disease, 2015)
Background: Previous studies have reported conflicting survival rates for connective tissue disease (CTD)-associated usual interstitial pneumonia (UIP) and idiopathic pulmonary fibrosis (IPF/UIP). This study investigated the differences in the clinical characteristics and prognoses of patients diagnosed with CTD-UIP and IPF/UIP. Methods: A retrospective review of patients with IPF (n=88) and CTD-UIP (n=67) from January 2008 to June 2013 was completed. We compared the demographics and clinical characteristics between the two groups. Survival rates were compared using a log-rank and Cox proportional hazard regression analysis. Results: Undifferentiated-CTD (UCTD) accounted for 33% of the established CTD-UIP cases. No significant differences were identified in the demographic characteristics or physiological parameters between the UCTD and CTD patients (all P>0.05). However, the CTD-UIP patients were more likely to be young, female, and nonsmokers compared with the IPF/UIP group (all P